Environmental Care and the Catholic Church - Álvarez Alonso, José (2026)
The Catholic Church has become involved in environmental issues relatively recently, beginning with the Second Vatican Council, which coincided with the rise of the environmental movement in the United States and Europe. Although various Church Fathers and theologians throughout history have addressed themes related to the "care" of Creation, concern for the environment has been largely absent from official doctrinal documents. The first pope to mention the global environmental crisis in an official document was Paul VI, in his 1971 encyclical Octogesima Adveniens, although it was John Paul II and, above all, Francis, who addressed the issue more, linking the ecological crisis to the economy and to phenomena such as consumerism and the global crisis of values. These last two popes developed innovative concepts such as «Catholic environmental ethics», «integral ecology», and the so-called «sins against Creation. » Pope Francis is the one who has taken the Church's commitment to environmental care to a new level, through encyclicals such as Laudato si and Laudate Deum, among other documents, and a multitude of messages and addresses, fostering an unprecedented environmental fervor among large sectors of the Catholic community. The Catholic Church currently plays an important role in promoting responsibility, environmental sustainability, and the values of environmental stewardship in a world where misinformation and the interests of economic groups contribute to climate change denial and the dismissal of the global environmental crisis.